Strengthening the Elderly’s Intellectual, Emotional, and Spiritual Intelligence: The Implementations of the Prophetic Sunnah - Maisarah Saidin; Latifah Abdul Majid; Siti Mardhiyah Kamal Azhar; Zulhilmi Mohamed Nor; Juliyana Junaidi (Universiti Sultan Azlan Shah, 2026)
Indexed by (Tier 1)